Self Care Education for Adolescent Women with Health Counseling and Disminore Exercise Training in an Effort to Optimize the Intensity of Disminore - Dessi, Dessi Novita Sari; Sonya Nelson; Arif Fadli Muchlis (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The problems that teenagers experience regarding menstruation are minor. Dysminorrhea is the most common disease complaint among young adult and adolescent women. The problems faced by partners are: Not many female students know dysmenorrhea exercises to overcome menstrual pain which is very helpful in non-pharmacological treatment and there is still a lack of female students' knowledge regarding self-care/good self-care during menstruation. The method used is in the form of lectures, question and answer discussions and presentations. The results of this service activity are an increase in health status, physical fitness and increasing knowledge and optimizing the intensity of dysmenorrhea in young women